Comparative analysis of physical development and body composition of kickboxing athletes with different training experience - Leonid Podrigalo; Shi Ke; Wojciech J. Cynarski; Volodymyr Perevoznyk; Volodymyr Paievskyi; Olexandr Volodchenko; Liudmyla Kanunova (Kharkiv State Academy of Physical Culture, 2023)
Background and Study Aim. Comparative analysis of physical development and body composition using the index method in kickboxing athletes with different training experience. Material and Methods. Participants: 30 kickboxing athletes, group 1 - 15 people, (13.20±0.60) years old, training experience (0.71±0.13) years. Group 2 - 15 people, (15.20±1.14) years old, training experience (6.80±1.16) years. 18 anthropometric indicators were determined. 21 indices were calculated based on them. The median (Me), 1 (25%) and 3 (75%) quartiles were determined. The somatotype was determined by the bioimpedance method using the OMRON BF-511 body composition monitor (Japan). The significance of differences in the groups was assessed by the nonparametric Rosenbaum test (Q). Results. A significant excess of indicators of the 2nd group in terms of Erisman's index (Q=10), Pignet's index (Q=7), Livy's index (Q=12), Isakson's body surface area (Q=11) and relative body surface (Q=21) was established , relative length of arm (Q=11) and leg (Q=14), index of arm circumference (Q=15) and leg (Q=6), shoulder index (Q=10), indices of massiveness of segments of the forearm (Q=11) and shoulder (Q=30), conditional moments of force of the forearm (Q=30), shoulder (Q=30), lower leg (Q=30) and thigh (Q=30). A trend towards a decrease in fat content and an increase in muscle tissue in more trained athletes has been confirmed. Conclusions. A comparative analysis of the physical development and body composition of kickboxing athletes with different training experience confirmed certain differences. More trained kickboxers had better indicators of the shoulder index, which reflects the posture of the athletes. The Erisman index illustrated the increase in the muscles of the torso under the influence of training loads. The increase in body surface area and relative body surface reflects the greater adaptive potential of more trained kickboxers. The large relative length of the arms and legs, the indices of the ratio of the segments of the limbs, the indices of massiveness and the conditional moments of the segments' strength reflect the best technical capabilities of more trained athletes, the ability to blow at a greater distance and with greater force. The adequacy of using the method of indices as more informative than anthropometric indicators is shown. It is proposed to use these indices in monitoring the state of kickboxing athletes.